HUKUM ISLAM DAN HUKUM POSITIF: ANALISIS TERHADAP TINDAK PERSEKUSI (STUDI KASUS DI DESA KEDUNGBOTO KECAMATAN BEJI KABUPATEN PASURUAN) - Ahmad Mudzakkir; Ach. Faisol; Khoirul Asfiyak (Jurnal Hikmatina, 2019)
The aim of this study is to find out the problems in cases study of persecution in which focus of the research as follow; 1) the process of persecution 2) analysis of persecution and 3) factors leading persecution.  To make specify goal, this study employs a qualitative approach, and the type of research is a case study. The results of this study, 1) the persecution in Kedungboto village is an action that often occurs and begins from the societies’ unconsciousness towards the law, so it appeared giving rise to vigilante actions, 2) the persecution started from the community and motivation needs to be grown to obey existing regulations. Thus, there is no arbitrary action, and 3) the factor leading persecution occurred due to the lack of awareness of the law and the limited the beliefs of society toward law enforcer. This makes the society become accustomed and often done. Kata Kunci: Hukum Islam, Hukum Positif, Tindak Persekusi